2017
DOI: 10.1002/mus.25754
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave treatment can selectively destroy end plates in neuromuscular junctions

Abstract: This localized destruction of end plates may be caused by differences in acoustic impedance induced by the density of acetylcholine receptors. These results provide a possible mechanism for the effectiveness of rESW treatment for spasticity and dystonia. Muscle Nerve 57: 466-472, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…Although still speculative, other researchers have concluded that rESWT produces a series of reactions such as increased capillary blood flow at the site of application, decreased muscle tension, reduced substance P [28], and, especially important for our study, direct suppression of pain receptors [26,62], which explains the fact that higher initial VAS scores correlated with greater treatment success. Greater pain increases the number of active nociceptors that increase local density and act as a reflective surface that generates more cavitations and a greater therapeutic effect.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although still speculative, other researchers have concluded that rESWT produces a series of reactions such as increased capillary blood flow at the site of application, decreased muscle tension, reduced substance P [28], and, especially important for our study, direct suppression of pain receptors [26,62], which explains the fact that higher initial VAS scores correlated with greater treatment success. Greater pain increases the number of active nociceptors that increase local density and act as a reflective surface that generates more cavitations and a greater therapeutic effect.…”
Section: Discussionmentioning
confidence: 67%
“…Such waves propagate in the form of threedimensional concentric hemispheres, following the laws of acoustics [24], by changing the properties of the medium it reaches, in cycles of compression (positive phase) and decompression (negative phase) [25]. It generates pressure forces concentrated at the tissue interfaces (skin, subcutaneous, fascia, muscle, and bone) and more intensely in areas of greater structural density (trigger point, motor end plate, areas of inflammation, or calcifications) [26][27][28][29].…”
mentioning
confidence: 99%
“…In the past, the mechanism by which ESWT acts on musculoskeletal diseases was assumed to be mechanical decomposition, just like extracorporeal shock wave lithotripsy. However, further clinical observations and experimental results, have suggested that ESWT can promote neovascularization, the release of growth factors, the differentiation of mesenchymal stem cells and the production of endogenous nitric oxides (NOs) [46][47][48], which can decrease the intrinsic stiffness of connective tissue, increase muscle elongation, improve tissue microcirculation and change the formation of neuromuscular junctions of the peripheral nervous system [49][50][51], in order to achieve encouraging clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, there is a universal consensus that ESWT improve spasticity and joint range of motion [3,[6][7][8][9][10][11][12][13][14][15][16][17][18]; and even Dymarek maintains that ESWT could also modify the Hmaximum/M-maximum ratio (evaluates the excitability of αmotor neuron) [6]. There is also a consensus that ESWT do not modify neurophysiological variables such as latency and amplitude of MUP, motor conduction velocity, neither the latencies nor amplitudes of the late responses; therefore, the mechanism of action of the ESWT remains a mystery [3,[6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, no study has assessed pre-or post-synaptic neuromuscular transmission of spastic muscle or the effect of ESWT on it, despite the fact that Kenmoku et al have shown that ESWT cause neuromuscular transmission dysfunction, evidenced by histological changes, as well as by changes in electron microscopy at the level of post-synaptic acetylcholine receptors, without causing any associated axonal or myofibrillar damage [11,12].…”
Section: This Article Is Part Of the Topical Collection On Medicinementioning
confidence: 99%